Kebijakan Pemerintah Kota Palembang melalui Sister City : Tantangan dan Hambatan - Kencana, Novia; Permatasari, Yuni; Putra, Raniasa (Jurnal Pemerintahan dan Politik, 2024)
This journal explores the Sister City cooperation initiated by the Palembang City Government to enhance regional potential across various sectors. It adopts an interdisciplinary approach, combining public administration and international relations studies. Public administration focuses on government policies and their implementation, while international relations examine diplomatic activities in Sister City partnerships involving Palembang with Houston (United States), Yangzhou (China), and Zhuang Zhou (China). The study employs public policy theory and the Sister City concept as analytical frameworks, using indicators from Minister of Home Affairs Regulation No. 25 of 2020 on regional and international cooperation. The research uses a literature review method, relying on secondary data such as articles, documents, regulations, and prior studies. It investigates the stages of policy implementation in Palembang’s diplomacy efforts through three Sister City partnerships. The partnerships with Yangzhou and Zhuang Zhou have reached the stage of signing a Memorandum of Understanding (MoU), while the cooperation with Houston remains in the exploratory phase. The findings indicate several challenges hindering the effectiveness of these partnerships, including limited technical expertise among personnel in international cooperation, poor coordination, inadequate human resources such as translators, and leadership transitions that disrupt policy continuity. These issues highlight the need for improved technical capacity and better coordination to optimize the outcomes of international collaborations.